Zero-voltage switching half-bridge pulse width modulation DC-DC converter with switched capacitor active snubber cell for renewable energy applications - Bodur, Haci; Yesilyurt, Huseyin; Ting, Naim Suleyman; Sahin, Yakup (WILEY, 2021)
In this paper, soft switching isolated half-bridge converter with a new active snubber cell that uses switched capacitor for renewable energy applications is proposed. The proposed snubber cell does not consist any magnetic element so that its structure is quite simple. Furthermore, the auxiliary switches in the proposed active snubber cell are exposed to only half of the input voltage. There is no additional voltage and current stress on any semiconductor devices. All semiconductor power devices in the proposed converter are operated by soft switching. The proposed converter is analyzed thoroughly, and the theoretical analyzes are affirmed by an implementation having 300-V-DC input, 20-V-DC output, 75-W output power, and 150-kHz switching frequency. The overall hard switching efficiency of the converter is increased from 86.4% to 92.9% by aid of the proposed soft switching snubber cell.
Keywords: half‐ bridge converter; hard switching; renewable energy; snubber cell; soft switching; zero‐ voltage switching; Engineering